Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1021/acsanm.9b00226
|View full text |Cite
|
Sign up to set email alerts
|

Nanolayered Cobalt@Carbon Hybrids Derived from Metal–Organic Frameworks for Microwave Absorption

Abstract: High-performance broadband microwave absorbers are greatly required to cope with the increasingly serious microwave radiation pollution. Integration of dielectric and magnetic components is a promising strategy to achieve desirable microwave absorption performance. Herein, we demonstrated a facile and efficient approach to fabricate two-dimensional cobalt@carbon (Co@C) hybrids by solvothermal synthesis of cobalt–metal–organic framework (Co-MOF) nanosheets and subsequent thermal pyrolysis for efficient microwav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(47 citation statements)
references
References 58 publications
3
44
0
Order By: Relevance
“…In this article, we found that, unlike other MOF derived carbon materials with single‐stage or double‐stage porous structure, 22,24–26 our CD‐MOF derived carbon has a hierarchical(three‐stage) porous structure, containing micro‐, meso‐, and macro‐pores simultaneously. In order to guide the preparation of CD‐MOF derived HPC, the relationship between the morphological properties and prepared conditions is studied in this article.…”
Section: Introductionmentioning
confidence: 87%
“…In this article, we found that, unlike other MOF derived carbon materials with single‐stage or double‐stage porous structure, 22,24–26 our CD‐MOF derived carbon has a hierarchical(three‐stage) porous structure, containing micro‐, meso‐, and macro‐pores simultaneously. In order to guide the preparation of CD‐MOF derived HPC, the relationship between the morphological properties and prepared conditions is studied in this article.…”
Section: Introductionmentioning
confidence: 87%
“…In general, when evaluating the absorbing properties of a material, it is necessary to consider the following three main factors: the minimal RL, the absorber thickness and e®ective absorption bandwidth (the RL intensity is below -10 dB, which means the absorption e±ciency is over 90%). [39][40][41] However, the minimum RL value of FP is only À7.86 dB at a frequency of 9.78 GHz with the thickness of 3.5 mm. It can be inferred that the construction of the double-shell structure can e®ectively improve the microwave absorbing properties.…”
Section: Resultsmentioning
confidence: 96%
“…Thus, only eddy current loss, natural resonance and exchange resonance need to be taken into consideration. If the factor C0 = μ″(μ′) −2 f −1 (f is the frequency) keeps constant, the eddy current loss will be the sole reason for magnetic loss 51,52 . As shown in Figure S5, C0 for all the samples displays frequent dependence, suggesting the contribution comes from natural resonance and exchange resonance besides eddy current loss.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the steep peak in the μ″ curve between 2-6 GHz may benefit from the natural resonance. The following peaks in higher frequencies are attributed to the exchange resonance 52,53 .…”
Section: Resultsmentioning
confidence: 99%